EKSPLORASI ETNOMATEMATIKA PADA JEMBATAN LAMA KEDIRI SEBAGAI SARANA BELAJAR MATEMATIKA SISWA - Rahmatul Risala Octaviandy Gresini; Jatmiko Jatmiko; Aris Taufik Febriansah; Lina Rihatul Hima (Dharma Pendidikan, 2025)
This study examines the application of ethnomathematics on the old Kediri bridge as a historical building that contains mathematical values. This study uses a qualitative descriptive method with an ethnographic approach to identify and describe mathematical concepts embedded in the form of the bridge building. The results of the study indicate that the old Kediri bridge contains geometric concepts that can be implemented in mathematics learning. Some geometric shapes found include triangles, rectangles, trapezoids. These geometric shapes can be used to teach the concept of area, circumference, angles and similarity. The conclusion is that the old Kediri bridge can be an interesting source of learning mathematics because it has historical elements, especially for geometry learning. By utilizing historical buildings as learning media, it is expected to improve students' understanding of mathematical concepts and enrich their learning experiences